Reflections: Service to Our Nation. (October 2015) - Goodman, Joseph
Service to others is something that physicians understand and undertake on a daily basis. Military physicians are in a unique role of serving both our patients and our nation. Millions of Americans have answered the call to military service since the attacks of September 11, 2001. As otolaryngologists, we will increasingly care for veterans of the Global War on Terror. Service to our nation is a mutual goal that brings together people from very different walks of life.